La privación de lo finito en A cielo abierto de João Gilberto Noll - Bylaardt, Cid Ottoni (Verbum – Analecta Neolatina, 2012)
This text intends to show how João Gilberto Noll’s writing is erratic and disperse due to the lack of limits within which the literary text may contain itself. Such writing is characterized by the excess of world in it, by the impossibility of intervening in the real world, imprisoned by an infinite that is a surplus, by a lack of finite. Talking about men and things in the periphery of the world and in the end of times, literature is not a serious aid in the domain of tasks, because it is not the result of a true work, it is not a kind of work that acts among the human beings. It is thus strange to every true culture, to true history, which is not made of a fictitious transformation.